2005
DOI: 10.1890/04-1830
|View full text |Cite
|
Sign up to set email alerts
|

Resorption Efficiency Decreases With Increasing Green Leaf Nutrients in a Global Data Set

Abstract: To investigate effects of green‐leaf nutrient status on senesced‐leaf nutrient concentrations and resorption efficiency, we developed a database of nitrogen (N) and phosphorus (P) concentrations in green and senesced leaves from 92 published studies. We fit power functions (i.e., [nutrient]sen = A [nutrient]grB) separately for N and P. The database encompassed 297 perennial species of different life‐forms. Across these divergent species and conditions, a major control on senesced‐leaf nutrient concentration wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

45
367
13
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(433 citation statements)
references
References 63 publications
45
367
13
8
Order By: Relevance
“…Internal retranslocation rates of N, P, and K occurred in all studied species, with high variation (N: from -16.86 to -49.25% / mean value = -34.41%; P: from -48.89 to -74.47% / mean value = -60.48%/ K: from -39.98 to -77.60% / mean value = -62.90%) ( Table 1). Internal retranslocation was a function of two factors: the low availability of these nutrients in all forest plantations soils (Table 3), which is frequently observed in most tropical soils, especially for N and P (Kobe, Lepczyk, & Iyer, 2005), and the high mobility of these nutrients in plant organisms.…”
Section: Resultsmentioning
confidence: 99%
“…Internal retranslocation rates of N, P, and K occurred in all studied species, with high variation (N: from -16.86 to -49.25% / mean value = -34.41%; P: from -48.89 to -74.47% / mean value = -60.48%/ K: from -39.98 to -77.60% / mean value = -62.90%) ( Table 1). Internal retranslocation was a function of two factors: the low availability of these nutrients in all forest plantations soils (Table 3), which is frequently observed in most tropical soils, especially for N and P (Kobe, Lepczyk, & Iyer, 2005), and the high mobility of these nutrients in plant organisms.…”
Section: Resultsmentioning
confidence: 99%
“…Different letters within a column indicate a significant difference at P < 0.05 Table 2. Results (P values) of three-way ANOVAs on the effects of species (S), N addition (N), P addition (P), and their interactions on nitrogen (N s ) and phosphorus (P s ) concentrations in senesced leaves, and nitrogen (NRE) and phosphorus (PRE) resorption efficiency N concentration in green leaves with increased N supply (Kobe et al 2005), implying that plants will absorb more N from soils and become less dependent on N resorbed from senescing leaves.…”
Section: Discussionmentioning
confidence: 99%
“…The results are less conclusive because some studies have shown a decrease in nutrient resorption with increases in soil N availability (Huang et al 2012), but others have shown a neutral effect (Soudzilovskaia et al 2007). Inter-species variation and soil nutrient status might be two important factors for the inconsistent responses (Kobe et al 2005). Furthermore, few studies investigated nutrient resorption responses to increased soil phosphorus (P) availability and to its interactions with increased soil N availability (Kozovits et al 2007), especially in grasslands (Lü and Han 2010).…”
mentioning
confidence: 99%
“…recycling of litter nutrients, nutrient resorption from senescing leaves) and improved nutrient acquisition (e.g. phosphorous) by forming mycorrhizal association (Aerts and Chapin-III, 1999;Kobe et al, 2005).…”
Section: Effect Of Nutrient Additionmentioning
confidence: 99%